If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r + -3 = 2r + -7 Reorder the terms: -3 + 7r = 2r + -7 Reorder the terms: -3 + 7r = -7 + 2r Solving -3 + 7r = -7 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. -3 + 7r + -2r = -7 + 2r + -2r Combine like terms: 7r + -2r = 5r -3 + 5r = -7 + 2r + -2r Combine like terms: 2r + -2r = 0 -3 + 5r = -7 + 0 -3 + 5r = -7 Add '3' to each side of the equation. -3 + 3 + 5r = -7 + 3 Combine like terms: -3 + 3 = 0 0 + 5r = -7 + 3 5r = -7 + 3 Combine like terms: -7 + 3 = -4 5r = -4 Divide each side by '5'. r = -0.8 Simplifying r = -0.8
| 0=-16t^2+40t-4 | | 9+3(2u-3)=-3(6u-6)+8u | | (x+8)(x+6)=32 | | 8(9b+4)=-32 | | 2-(2c+3)=-3(3c-4) | | 2/3b9 | | (3x+5)(9x-5)=0 | | 2x^2+3x-2x-3=18 | | 11.5(4+X)= | | 5z+5=6-4z+17 | | 6=a+9 | | sec*x-secx-2=0 | | 2(2y+1)=(5y-2) | | 5x+9+4x=9+8+(-7) | | log(9x^3)=2 | | 7a^2-5a-5=-5 | | X^2-25=10 | | 2(25-5)=2(26+5) | | 5x+9+4x=9+8 | | 21/3×5-11 | | 2/7=x/7 | | (X^-3y^3)^-4/(y^3x^-5)^-5 | | 8x^(13/3)-24=0 | | 2*cosx=2*cos*2x | | 12z-4x=-7 | | 10h-10=10-10h | | x^9/2 | | 38x+66=180 | | 3x-(5x)= | | 2n-4=5n+5 | | 80x^2-720=0 | | 8=3x+bx |